2018
DOI: 10.1016/j.jsv.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Natural oscillations of a gas bubble in a liquid-filled cavity located in a viscoelastic medium

Abstract: The present study is motivated by cavitation phenomena that occur in the stems of trees. The internal pressure in tree conduits can drop down to significant negative values. This drop gives rise to cavitation bubbles, which undergo high-frequency eigenmodes. The aim of the present study is to determine the parameters of the bubble natural oscillations. To this end, a theory is developed that describes the pulsation of a spherical bubble located at the center of a spherical cavity surrounded by an infinite soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Figure 6 shows the temporal evolution of the bubble radius for D/R 0 ≈ 19, K = 6.5 × 10 −4 ( kD ≈ 1.68), P a = 4, and We = 7. We observe that the amplitude of the oscillation is indeed larger than the results from DNS in an unbounded domain, indicating the appearance of local resonance established between the bubble and the tube wall similar to the one reported in previous works of bubbles in closed pores [39].…”
Section: Wall Effectssupporting
confidence: 86%
“…Figure 6 shows the temporal evolution of the bubble radius for D/R 0 ≈ 19, K = 6.5 × 10 −4 ( kD ≈ 1.68), P a = 4, and We = 7. We observe that the amplitude of the oscillation is indeed larger than the results from DNS in an unbounded domain, indicating the appearance of local resonance established between the bubble and the tube wall similar to the one reported in previous works of bubbles in closed pores [39].…”
Section: Wall Effectssupporting
confidence: 86%
“…Bubble dynamics has been investigated for many years, and various models have been developed to describe the motion of bubbles in aqueous media [10] , [11] , [12] , near a rigid/elastic surface [13] , and in a tube [14] , [15] . In recent years, cavitation phenomena that occur in fully confined liquids has received more attention [16] , [17] , [18] , [19] , [20] , and models have been developed to understand the motion of fully confined bubbles in a liquid cavity, and the medium surrounding the cavity is considered to be an elastic/viscoelastic solid [21] , [22] , [23] , [24] , [25] , [26] , [27] . It is motivated mainly by applications in biology.…”
Section: Introductionmentioning
confidence: 99%
“…Sap cavitation occurs when the tree’s pumping system is operating under a negative pressure less than the threshold pressure [19] , [20] . For this interesting phenomenon, theoretical models of a bubble locate at the center of a spherical liquid cavity surrounded by solid medium were developed to investigate the behaviors of the bubble, such as the vibration frequency and attenuation of acoustic emissions related to cavitation bubbles inside trees [22] , [23] , [24] . In these researches, the breathing mode of cavitation bubbles is considered be the dominant mode, and it was found that the natural frequency of the bubble oscillation increases with the bubble radius, which is different from the case of unbounded liquid.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 In particular, the formation of bubbles within confined nano/micro-fluids is a growing field which has largely only been discussed theoretically. [47][48][49][50][51][52] Experimentally, the cavitation of bubbles has been explored in droplets of the order ∼ 20-150 µm. [53][54][55] It is unclear how the droplet size influences the evolution of gas nanobubbles produced from a droplet reaction.…”
mentioning
confidence: 99%